CLASS EXPLOITATION IN RON RASH’S SERENA NOVEL: A MARXIST CRITICISM - Nurman, Muniralizah; Kuncara, Singgih Daru; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This study examined Serena novel written by Ron Rash as the object of the research. The aimed of this research was to find out the portrayal of class distinction and labor exploitation in the novel. To achieve the purposes of the study, the research applied Marx’s Social Class and Exploitation theory, and International Labor Organization or ILO’s Indicators of Labor Exploitation. This research used descriptive qualitative research method and Marxist criticism to analyze the social issue of class exploitation reflected in the novel. The data in this research were words, phrases, sentences and paragraphs that indicated social class and exploitation. The result of this research showed two social classes, they were bourgeoisie and proletariat. Bourgeoisie referred to Serena, Pemberton, Buchanan and Wilkie who were owner of timber business, while proletariat were the workers whose life only depended on bourgeoisie for employment. Meanwhile, there were four forms of labor exploitation. First was excessive working hour, like worked eleven hours shift a day and only fifteen minutes break. Second was low salary, like cheap labor and inappropriate wages. Third was bad living condition, like limited and uncomfortable living condition, live in cheap and ragged wooden boxcar. And fourth was hazardous work, like no safety equipment, manual and dangerous tools, forced to work in moody ground and against extreme cold.Keyword: Marxist criticism, Capitalism, Class distinction, Exploitation, Mode of production.